The Effect of Pilates Exercise on Reducing Menstrual Pain in Adolescents: Literature Study - Eva Zulisa; Esa Zahirah; Lenny Irmawaty Sirait; Eva Sri Rahayu; Inna Noor Inayati (CV. Get Press Indonesia, 2024)
Dysmenorrhea, or menstrual pain, is common among adolescents, with global prevalence rates reaching 59.7% to 92%. This pain, affecting the lower abdomen, back, and groin, usually begins 24 hours before menstruation and can last up to three days. Management includes pharmacological options like NSAIDs and analgesics, as well as non-pharmacological approaches. Pilates exercise is a practical, non-drug option shown to reduce menstrual pain by stimulating endorphin production, providing a natural sense of relief and comfort. Purposes : The goal of this study is to ascertain whether Pilates exercises can help adolescents who are experiencing menstrual pain. Methods : The design of this study is a literature review. Search for published articles on Google Scholar, Pubmed and GARUDA with the keywords